MEMBER REGISTRATION SYSTEM IN KOPERASI PEGAWAI NEGERI KECAMATAN PONDOK GEDE USING MICROSOFT ACCESS 97 - Indria Panca Kusuma; Noveandi Rahayu, SKom, MM. (Jurnal Sistem Informasi, 2006)
In this scientific writing authors describe the design of Registration System for Civil Servants Cooperative Members in Sub Pondok Gede it using Microsoft Access.